2022
DOI: 10.52494/opcn8135
|View full text |Cite
|
Sign up to set email alerts
|

beware-of-triple-whammy

Abstract: The term "triple whammy" refers to a drug interaction following the concurrent use of angiotensinconverting enzyme inhibitors or angiotensin-II receptor blockers, diuretics and non-steroidal antiinflammatory drugs, the combination of which greatly increases the odds of acute kidney injury.Here, we report a case of a 66-year-old gentleman who was admitted into a tertiary care hospital for elective orthopaedic intervention. He had previously been prescribed sacubitril/valsartan and frusemide and had newly been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The term "triple whammy" was first introduced by Merlin C. Thomas in 2000, and refers to the simultaneous use of angiotensin-converting enzyme inhibitors (ACE-I) or angiotensin receptor blockers (ARB), diuretics, and NSAIDs, or selective cox-2 inhibitors [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "triple whammy" was first introduced by Merlin C. Thomas in 2000, and refers to the simultaneous use of angiotensin-converting enzyme inhibitors (ACE-I) or angiotensin receptor blockers (ARB), diuretics, and NSAIDs, or selective cox-2 inhibitors [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the risk of AKI after a triple whammy, showing that the highest risk occurs within the first 30 days and then decreases [14][15][16][17][18][19][20]. Only a 2022 Japanese study reported the time to onset of AKI [18].…”
Section: Discussionmentioning
confidence: 99%